An atypical sarcoidosis involvement in FDG PET/CT: A case report. Issue 52 (December 2016) - Robin, Philippe; Benigni, Paolo; Feger, Benoit; Salaun, Pierre-Yves; Abgral, Ronan
Abstract: Rationale: Sarcoidosis is an idiopathic systemic inflammatory granulomatous disorder comprised of epithelioid and multinucleated giant cells with little necrosis which involve various organs. Laryngeal involvement is extremely rare, with a prevalence of about 0.5 to 1%. Diagnoses: Here we present a case of laryngeal involvement of sarcoidosis demonstrated on 18 F-Fluorodesoxyglucose Positron-Emission Tomography/Computed Tomography (FDG PET/CT). Patient concerns: A 63 year-old man suffering from dysphonia was referred to our department for characterization of laryngeal lesion suspicious for cancer with non-informative biopsy, the sample was not sufficient for diagnosis. Interventions: FDG PET/CT showed a pathological uptake on the right vocal cord, but also highlighted a bilateral uptake in intrathoracic hilar lymphadenopathy areas, typically found in several inflammatory diseases. Outcomes: New laryngeal targeted biopsies revealed non-caseating epithelioid granulomas suggesting sarcoidosis involvement. After 6 months of systemic steroid treatment, FDG PET/CT showed a significant decrease of the laryngeal uptake. Lessons: This case shows the usefulness of FDG PET/CT to accurately assess inflammatory activity in rare extra-pulmonary sarcoidosis involvement. Moreover, this case emphasizes that FDG PET/CT is an interesting tool for assessing therapeutic efficacy of inflammatory diseases such as sarcoidosis.